2003
DOI: 10.1034/j.1600-0714.2003.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive, multifocal oral verrucous leukoplakia: proliferative verrucous leukoplakia or not?

Abstract: In retrospect, none of the cases fulfilled the original PVL criteria, although three cases were suggestive of PVL. Nevertheless, these findings do not necessarily preclude the existence of PVL as a clinicopathological entity in Malaysian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
17

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 38 publications
1
64
0
17
Order By: Relevance
“…The results of the various case series are shown in table 1. Among the found series, the authors of the study by Ghazali et al (22) were not able to confirm that their cases could be diagnosed as PVL. Therefore, this series was not included in the table.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The results of the various case series are shown in table 1. Among the found series, the authors of the study by Ghazali et al (22) were not able to confirm that their cases could be diagnosed as PVL. Therefore, this series was not included in the table.…”
Section: Resultsmentioning
confidence: 68%
“…Generally, diagnosis is made according to Hansen's first definition of PVL in 1985, not taking into account the latter ones. This creates doubt about whether all published PVL cases are indeed PVL, as has been stated by several authors (22)(23)(24). As a result of this, we find it necessary to elaborate specific diagnostic criteria for PVL.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Ghazali et al, [23] suggested the following criteria for the diagnosis of PVL: It also helps in excluding other recognized white lesions. The site of the biopsy should be from symptomatic area and if the lesion is asymptomatic, it should be taken from red or indurated areas [4,17].…”
Section: Leukoplakia and Epstein Barr Virus (Ebv)mentioning
confidence: 99%